Factors associated with disease-specific survival of patients with non-small cell lung cancer - Mirian Carvalho de Souza; Oswaldo Gonçalves Cruz; Ana Glória Godoi Vasconcelos (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: Lung cancer is a global public health problem and is associated with high mortality. Lung cancer could be largely avoided by reducing the prevalence of smoking. The objective of this study was to analyze the effects of social, behavioral, and clinical factors on the survival time of patients with non-small cell lung cancer treated at Cancer Hospital I of the José Alencar Gomes da Silva National Cancer Institute, located in the city of Rio de Janeiro, Brazil, between 2000 and 2003. Methods: This was a retrospective hospital cohort study involving 1,194 patients. The 60-month disease-specific survival probabilities were calculated with the Kaplan-Meier method for three stage groups. The importance of the studied factors was assessed with a hierarchical theoretical model after adjustment by Cox multiple regression. Results: The estimated 60-month specific-disease lethality rate was 86.0%. The 60-month disease-specific survival probability ranged from 25.0% (stages I/II) to 2.5% (stage IV). The performance status, the intention to treat, and the initial treatment modality were the major prognostic factors identified in the study population. Conclusions: In this cohort of patients, the disease-specific survival probabilities were extremely low. We identified no factors that could be modified after the diagnosis in order to improve survival. Primary prevention, such as reducing the prevalence of smoking, is still the best method to reduce the number of people who will suffer the consequences of lung cancer.